Robinson Crusoe (Young Reading) - Wilkes,Angela (Uk Usborne Publishing Ltd, 2003)
The classic story re-told for children growing in reading confidence. Follows the adventures of Robinson Crusoe, who survives a shipwreck only to find himself stuck of a desert island! How will he manage alone? Featuring the colourful illustrations of Peter Dennis. Part of the Usborne Reading Programme developed with reading experts at the University of Roehampton.